Causal associations of cognition, intelligence, education, health and lifestyle factors with cervical spondylosis: a mendelian randomization study - Ren, Zhenxiao; Cheng, Xing; Xu, Jinghui; Niu, Tianzuo; Long, Houqing (Frontiers in Genetics, 2024)
Background: Education, cognition, and intelligence are phenotypically and genetically related. Education has been shown to have a protective effect on the risk of developing cervical spondylosis. However, it is unclear whether cognition and intelligence have independent causal effects on cervical spondylosis, and whether underlying risk factors influence this association. Methods: We first assessed the independent effects of education, cognition, and intelligence on cervical spondylosis by two-sample Mendelian randomization and multivariable Mendelian randomization analysis, and evaluated 26 potential association mediators using two-step Mendelian randomization, and calculated the median proportion. Results: The results showed that only education had an independent causal effect on cervical spondylosis, and had a protective effect on the risk of cervical spondylosis (β: -0.3395; se: 0.166; P<0.05; OR:0.71; [95%CI: 0.481-0.943]. Of the 26 potential associated mediators, a factor was identified: SHBG (mediated proportion: 2.5%). Univariable Mendelian randomization results showed that the risk factors for cervical spondylosis were time spent watching TV (OR:1.96; [95%CI: 1.39-2.76]), smoking (OR:2.56; [95%CI: 1.061-1.486]), body mass index (OR:1.26; [95%CI: 1.124-1.418]), percentage of body fat (OR:1.32; [95%CI: 1.097-1.593]), major depression (OR:1.27; [95%CI: 1.017-1.587]) and sitting height (OR:1.15; [95%CI: 1.025-1.291]). Protective factors include computer using (OR:0.65; [95%CI: 0.418-0.995]), sex hormone binding globulin (OR:0.87; [95%CI: 0.7955-0.951]) and high-density lipoprotein (OR:0.90; [95%CI: 0.826-0.990]). Conclusions: Our findings demonstrate the causal and independent effects of education on cervical spondylosis and suggest that lifestyle media may be a priority target for the prevention of cervical spondylosis due to low educational attainment.